Sistem Pemantauan Suhu, Kelembapan Udara dan pH Air pada Rumah Anggur berbasis Internet of Things Menggunakan Aplikasi Website - Mislaini Mislaini; Ikhwan Ruslianto; Kasliono Kasliono (STMIK Budi Darma, 2023)
Grapes are plants that are difficult to grow in tropical climates. It requires specific enviromental conditions as well as special care, with optimal growth of grapes occuring in lowlands (0-300 masl) with a humidity score ranging from 75% - 80% humidity and temperatures between 23°C - 31°C, and a water pH level from 5.5 pH - 7.3 pH. To achieve these ideal conditions, technology in the form of an Internet of Things (IoT) system and a greenhouse is used in order to monitor and control the grapes' growing environment. The use of this technology aims to improve efficiency and productivity by taking into account the temperature, humidity and water pH level as factors which affect the growth, quality, and yield of grapes. Research result shows that the use of IoT technology in controlling temperature and humidity air effectively increases the productivity of grapes. This can be seen from the increase in the number of leaves, stem length, and number of shoots on grapes that were monitored and controlled by the IoT system. The results of testing the accuracy of each sensor by conducting 15 experiments show that the average water pH measurement accuracy is 0.1%, while temperature measurements and air humidity has an average accuracy of 0.1% and 0.3% respectively. In addition, the average response time of the system in controlling mist makers, fans and pumps alkaline is 3 seconds based on 15 tries.